Cutting-edge innovations and sustainable catalysts for fuel cells and electrolyzers: a comprehensive review - Chrouda, Amani; Almoteiry, Ahlam; AL-Saleem, Nouf K.; Slimi, Khalifa; Öztop, Hakan Fehmi (Elsevier Sci Ltd, 2026)
This review offers an in-depth analysis of catalyst technologies for fuel cells and electrolyzers, emphasizing their pivotal role in driving sustainable energy advancements. It opens with a clear overview of its scope and objectives, followed by a detailed explanation of the core principles governing fuel cells and electrolyzers, with a focus on catalyst functionality. The paper delves into recent progress in catalyst development, covering PGMbased materials, non-precious metal alternatives, single-atom catalysts, bimetallic and alloy systems, as well as nanostructured and high-entropy catalysts. It further explores sustainable design approaches, including bioinspired solutions, eco-friendly synthesis methods, recycling practices, and the use of alternative feedstocks. The review outlines key strategies to boost catalyst efficiency, such as surface engineering, structural optimization, hybridization, and techniques to enhance durability and long-term stability. It also addresses current challenges and research gaps, identifies technological limitations, and highlights emerging trends and industrial prospects. The paper concludes by synthesizing major findings and reaffirming the vital contribution of sustainable catalyst innovations to the future of clean energy technologies.
Keywords: Fuel cells & electrolyzers; Platinum group metals (PGM); Non-precious metal catalysts (NPMCs); Single-atom catalysts (SACs); Bimetallic catalysts; Alloy catalysts; Nanostructured catalysts; High-entropy catalysts; Bio-inspired catalysts; Hybrid catalysts; Hybrid catalysts